THE SEGREGATION PATTERN OF INSECT RESISTANCE GENES IN THE PROGENIES AND CROSSES OF TRANSGENIC ROJOLELE RICE - Satoto, Satoto; Sulistyowati, Yuli; Hartana, Alex; -Loedin, Inez H. Slamet (Indonesian Journal of Agricultural Science, 2008)
Successful application of genetic transformation technique, especially in developing rice variety resistant to brown plant hopper and stem borer, will depend on transgene being expressed and the gene inherited in a stable and predictable manner. This study aimed to analyse transgene segregation pattern of the progenies and the crosses of transgenic rice cv. Rojolele harboring cry1Ab and gna genes. The third generation (T2) of fivetransgenic Rojolele events containing gna and/or cry1Ab were evaluated for two generations to identify the homozygous lines and to study their inheritance. The homozygous lines were selected based on the result of PCR technique. The segregation patterns of gna and cry1Ab were studied in eight F2 populations derived from Rojolele x transgenic Rojolele homozygous for cry1Ab and or gna and their reciprocal crosses. DataÂ  resulted from PCR of F2 population were analysed using a Chi Square test.The study obtained six homozygous lines for gna, namely A22- 1-32, A22-1-37, C72-1-9, F11-1-48, K21-1-39, K21-1-48, and two homozygous lines for cry1Ab, namely K21-1-39 and K21- 1-48. Both cry1Ab and gna transgenes had been inherited through selfing and crossing with their wild type as indicated from the F1 containing gna and cry1Ab as many as 48.4% and 47.4%, respectively. In six of the eight crosses, gna was inherited in a 3:1 ratio consistent with Mendelian inheritance of a single dominant locus, while in the remaining two crosses, gna was segregated in a 1:1 ratio. The presence of cry1Ab in F2 populations also showed a 3:1 segregation ratio in all crosses. In the F2 population derived from F1 plant containing cry1Ab and gna, both transgenes segregated in a 9:3:3:1 dihybrid segregation ratio. This study will add to the diversity of geneticsources for insect resistance and allow further use of these transgenic lines for pyramiding resistance to brown plant hopper and stem borer orÂ  separately in rice breeding programs whenever the efficacy tests and biosafety requirements have been completed.